Rapid Land Cover Change in The South Sumatera Peat Area Associated With 2015 Peat Fires - Raden Putra; Tastaptyani K Nufutomo; Yuni Lisafitri; Novi K Sari; Alfian Zurfi; Deni O Lestari; Muhammad U Nuha (Journal of Geoscience, Engineering, Environment, and Technology, 2022)
The peat fire events in Indonesia, particularly the South Sumatra area, changed the appearance of surface vegetation. The fires usually occur during the dry season from July to October. This study aims to evaluate land cover changes due to 2015’s peat fire in the South Sumatra peatlands. Remote sensing techniques using a Normalized Difference Vegetation Index (NDVI) method were used to identify the change of vegetation density in the study area. The results showed that 69% of the total South Sumatra peatland was burned due to the 2015 peat fire event. The level of vegetation density was considerably decreased by fire events. The degradation in the burned area was dominated by land cover class of ferns/shrub. The Peat fires during the observation period have a negative impact on the peat ecosystem, so improvements are needed in peatland management practices. Improvements need to be made in fire prevention and management practices, as well as restoration of burnt land.